The feasibility of managing telework for expansion - Brick, Darren (My University, 2019)
The purpose of this consultancy report is to analyse the feasibility of expanding SearchKings Africa’s footprint in Cape Town by having a more physical presence in the region through the use of telework. Telework can be a powerful offering which can be cost effective and offer a wide range of benefits if managed and implemented correctly. If not, it can be costly and cause reputational damage to a business. This report has reviewed previous literature to understand if telework should be offered to all employees, what impact technology has on managing a teleworker, the issues and benefits of teleworking, what makes a teleworker successful, and what the managerial implications of teleworking are. A further review of other consultancy reports in the areas of telework and digital workplaces was conducted to provide additional insights into the landscapes and learnings of others who have analysed the dynamics of telework. These reviews were assessed to identify the most appropriate strategic models to use in the current organisational environment of SearchKings. A cross-sectional quantitative analysis was used to derive descriptive and inferential statistics through the use of an online survey. The survey was sent out to managers of teleworkers and provided data-driven insights into the current South African telework landscape. These findings proved as well as disproved findings from previous literature and consultancy reports and provided localised insights into the current telework environment. The findings provided insights into who the most suitable people would be to telework, managers’ perceptions of the current benefits and challenges of telework, and the managerial and organisational implications of telework.
MBA
Keywords: Telework, remote work, distance work, satellite office, remote office, digital workplace.